Предмет: Алгебра,
автор: kkk26j
упростите выражение (2x+1)^2-4(x-3)(3+x)
Ответы
Автор ответа:
0
(2x+1)²-4(x-3)(3+x)=(2x+1)²-4(x-3)(x+3)=
=(4x²+4x+1)-4(x²-9)=4x²+4x+1-4x²+36=4x+37
Otvet: 4x+37
Formuli: (a+b)²=a²+2ab+b², a²-b²=(a+b)(a-b)
=(4x²+4x+1)-4(x²-9)=4x²+4x+1-4x²+36=4x+37
Otvet: 4x+37
Formuli: (a+b)²=a²+2ab+b², a²-b²=(a+b)(a-b)
Похожие вопросы
Предмет: Українська мова,
автор: pavlenkomatvij4
Предмет: Английский язык,
автор: Secret123456789
Предмет: Математика,
автор: xhuuyfucj
Предмет: Биология,
автор: Аноним
Предмет: Биология,
автор: nver7575